2015
DOI: 10.1016/j.cell.2015.10.041
|View full text |Cite
|
Sign up to set email alerts
|

K-Ras Promotes Tumorigenicity through Suppression of Non-canonical Wnt Signaling

Abstract: K-Ras and H-Ras share identical effectors and have similar properties; however, the high degree of tumor-type specificity associated with K-Ras and H-Ras mutations suggests that they have unique roles in oncogenesis. Here, we report that oncogenic K-Ras, but not H-Ras, suppresses non-canonical Wnt/Ca(2+) signaling, an effect that contributes strongly to its tumorigenic properties. K-Ras does this by binding to calmodulin and so reducing CaMKii activity and expression of Fzd8. Restoring Fzd8 in K-Ras mutant pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
188
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 178 publications
(200 citation statements)
references
References 58 publications
10
188
0
2
Order By: Relevance
“…Two studies have shown that PKC activators can suppress the growth of K-Ras tumors in nude mice by stimulating K-Ras phosphorylation (39,57). Similarly and consistent with the loss of phosphorylated K-Ras from the PM as a result of prolonged activation of PKG, we observed inhibition of cell proliferation in KRas-positive NSCLC cells upon chronic activation of the AMPK ¡ eNOS ¡ sGC ¡ PKG signaling pathway.…”
Section: Discussionsupporting
confidence: 88%
“…Two studies have shown that PKC activators can suppress the growth of K-Ras tumors in nude mice by stimulating K-Ras phosphorylation (39,57). Similarly and consistent with the loss of phosphorylated K-Ras from the PM as a result of prolonged activation of PKG, we observed inhibition of cell proliferation in KRas-positive NSCLC cells upon chronic activation of the AMPK ¡ eNOS ¡ sGC ¡ PKG signaling pathway.…”
Section: Discussionsupporting
confidence: 88%
“…They also showed that diminishing the charge on the polybasic region by stimulating phosphorylation of S181 with bryostatin-1 enhances the ability of PDEδ to solubilize KRAS4b. Recent studies have also shown that KRAS suppresses Wnt/Ca 2+ signaling pathway by direct binding with calmodulin and that the KRAS4b-calmodulin interaction is attenuated by phosphorylation of S181 by PKC (39,40). Our structural data show that six lysine residues present between 175 and 180 do not interact with PDEδ and thus, are not likely to play any role in KRAS4b-PDEδ interaction.…”
Section: Discussionmentioning
confidence: 49%
“…It was recently suggested that K-ras is the major driver of stem cell or progenitor cell proliferation, while H-ras drives differentiation (75)(76)(77). Therefore, SPRED1's well-documented role in regulating differentiation (2) may integrate in the following way, according to our differential Ras regulation scenario outlined above.…”
Section: Discussionmentioning
confidence: 96%